2001
DOI: 10.1002/1097-0290(20010320)72:6<611::aid-bit1026>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein secretion biotechnology usingStreptomyces lividans: Large-scale production of functional trimeric tumor necrosis factor ?

Abstract: We evaluated the feasibility of large‐scale production of biopharmaceuticals expressed as heterologous polypeptides from the Gram‐positive bacterium Streptomyces lividans. As a model protein we used murine tumor necrosis factor alpha (mTNFα). mTNFα fused C‐terminally to the secretory signal peptide of the subtilisin‐inhibitor protein from Streptomyces venezuelae. Under appropriate fermentation conditions, significant amounts of mature mTNFα (80–120 mg/L) can be recovered from spent growth media. Efficient down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…Streptomyces lividans has been used for the heterologous secretion of several polypeptides of bacterial and eukaryotic origin (for examples see [ 1 5 ]). Commonly, heterologous genes are fused to signal peptide sequences from highly expressed/secreted endogenous Streptomyces proteins [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomyces lividans has been used for the heterologous secretion of several polypeptides of bacterial and eukaryotic origin (for examples see [ 1 5 ]). Commonly, heterologous genes are fused to signal peptide sequences from highly expressed/secreted endogenous Streptomyces proteins [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that S. lividans can efficiently secrete active trimeric murine tumor necrosis factor alpha (mTNFα) [ 5 , 10 ], a Jonesia sp. xyloglucanase of 100 kDa [ 1 ] and other polypeptides such as phospholipase D [ 3 ], transglutaminase (TGase), β-1,4-endoglucanase and β-glucosidase [ 11 ] into the growth medium.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to S. lividans exhibiting less extracellular proteolytic activity and also a lack of the strong restriction system of S. coelicolor [ 11 – 13 ]. Some important enzymes, as well as recombinant proteins are produced by Streptomyces , including the murine tumour necrosis factor alpha (mTNFα) [ 12 , 14 , 15 ] and human glucagon [ 16 ]. For an overview of recombinant protein production and some recent examples of heterologous (mammalian and microbial) proteins produced using S. lividans as the host organism, as well as how systems biology (including metabolomics) approaches can be developed to improve protein production, the reader is directed to the following excellent reviews [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of reports concerning the secretory production system using S. lividans as the host [ 13 - 16 ]. The secretory production of useful protein is one of practical ways for industrial protein production due to the simple purification procedures that proteins could be purified directly from the culture broth [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are a large number of reports concerning the secretory production of useful proteins using S. lividans as the host. Pozidis et al successfully used it to produce a biopharmaceutical, mTNFa, derived from mouse [ 14 ]. Zhang et al reported the secretory production of human interleukin-4 receptor [ 15 ].…”
Section: Introductionmentioning
confidence: 99%